1994
DOI: 10.1161/01.cir.89.4.1819
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary versus intravenous effects of cocaine on coronary flow and ventricular function.

Abstract: We conclude that the effects of acute cocaine exposure on ventricular function are predominantly direct but of brief duration and therefore probably not clinically relevant. The effects of cocaine on coronary tone are predominantly indirect and biphasic, with early vasodilation followed by mild and more prolonged vasoconstriction. In the absence of coronary stenosis or ventricular hypertrophy, this small amount of vasoconstriction is unlikely to cause ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These new MCE data in humans also extend previous animal studies in several important ways. Our data: a) are consistent with earlier studies in anesthetized dogs 41-43 and pigs 44-46 showing decreased coronary blood flow, and decreased myocardial perfusion by Thallium scintography 47 as well as conventional (i.e., radiolabelled) microspheres 41, 47, 48 ; but b) differ at first glance from more recent studies in conscious dogs and non-human primates in which proximal coronary artery flow increased with cocaine (suggesting that the decreased flow in earlier studies was an artifact of anesthesia). 49 In the later study, however, coronary sinus pH fell despite increased large artery flow, suggesting impaired microvascular perfusion— which we have now shown directly in conscious humans.…”
Section: Discussionsupporting
confidence: 93%
“…These new MCE data in humans also extend previous animal studies in several important ways. Our data: a) are consistent with earlier studies in anesthetized dogs 41-43 and pigs 44-46 showing decreased coronary blood flow, and decreased myocardial perfusion by Thallium scintography 47 as well as conventional (i.e., radiolabelled) microspheres 41, 47, 48 ; but b) differ at first glance from more recent studies in conscious dogs and non-human primates in which proximal coronary artery flow increased with cocaine (suggesting that the decreased flow in earlier studies was an artifact of anesthesia). 49 In the later study, however, coronary sinus pH fell despite increased large artery flow, suggesting impaired microvascular perfusion— which we have now shown directly in conscious humans.…”
Section: Discussionsupporting
confidence: 93%
“…First, cocaine, due to its adrenergic stimulation, causes an increase in heart rate, blood pressure, and LV contractility [129]. Second, documented in several animal studies [98,[130][131][132][133][134][135] is coronary vasoconstriction associated with cocaine use, due to the stimulation of coronary arterial-adrenergic receptors [136,137]. These studies demonstrated that cocaine administered intravenously caused a decrease in coronary artery caliber and decreased coronary blood flow.…”
Section: Cardiovascular Toxicitymentioning
confidence: 96%
“…In this study, plasma cocaine concentrations were similar to the levels achieved in our study. Similarly, Zimring [10], in an anaesthetized pig model, found a decrease of 48% in the segment shortening, independent of changes in the coronary blood flow. The reduction of the left ventricular function was observed even when the coronary perfusion pressure was kept constant.…”
Section: Discussionmentioning
confidence: 81%
“…Cocaine also causes coronary vasoconstriction by two mechanisms, one secondary to the adrenergic stimulation itself, and a second one, independent of cathecolamines, owing to an enhanced calcium transport into the vascular smooth muscle [9]. It has been speculated that in patients with previous coronary artery disease, the coronary vasoconstriction provoked by cocaine superimposed to a fixed coronary stenosis, along with the increased oxygen consumption, could explain the cocaine‐induced myocardial ischaemia and, as a consequence, the left ventricular dysfunction [10,11]. However, both clinical as well as experimental data suggest that, besides the ischaemia, several other mechanisms including a direct depressant effect may also play a role in the cocaine‐induced left ventricular dysfunction [12,13].…”
Section: Introductionmentioning
confidence: 99%